PHOTOCATALYTIC DEGRADATION OF EOSIN Yellowish DYE IN AQUEOUS SOLUTION USING TITANIUM DIOXIDE AS CATALYST: IMPACT OF VARIOUS PARAMETERS AND KINETIC STUDY - SALIH, RAAD N.; KHALO, AKRAM A. HAJI, IDREES S.; AHMED, HOZAN A. (Journal of Duhok University, 2023)
Eosin Yellow, a type of heterocyclic dye consisting of bromine atoms, finds its applications in various industries, such as dyeing, printing, leather industry, and fluorescent pigment production. This study investigated the process of photocatalytic degradation of eosin yellowish dye in water solutions using titanium dioxide as a catalyst, as well as its degradation in the absence of semiconductors. The effect of specific factors including initial concentration of eosin yellowish dye and photo catalyst (TiO2), pH levels, and temperature on this degradation process was also tested. The results showed that increasing the concentration of TiO2 improved the above dye degradation. Moreover, it is found that shifting the pH from acidic to alkaline conditions enhanced dye degradation. This study also determined the order of eosin yellowish dye using integral rate laws and established that the degradation of the dye follows a first-order reaction at 517 nm